(untitled) (El Taco en la Brea, 2022)
This paper examines the crossovers between literary language and the violence of legal discourse in writings produced in prison. All of the texts, writing workshops, and scenes of production analyzed take place in the Devoto University Center, headquarters of the Buenos Aires University in the Penitentiary Complex of the same city. The materials that make up this corpus are heterogeneous in nature, yet strongly rooted in the literary realm: literary workshop experiences, texts created in a publishing workshop, written materials categorized as stories and manifestos. While legal discourse imposes a precise ordering of bodies and positions, literary writing offers a means of combatting this asphyxia; it provides a margin precisely where current regulations participate in policies of exclusion and death. In the analyzed texts, those who write while in incarceration draw on literature in order to construct places of enunciation, both precarious and political, from which to dispute meaning in regards to the law, justice and, to some extent, literature itself. In so doing, they mobilize literature as a tool to expose and contest forms of violence that stem from the contemporary punitive rationale.